New Moon's Visibility and International Islamic Calendar for the American Region 1407H - 1421H: By Mohammad Ilyas. Penang, Malaysia: The International Islamic Calendar Programme, n.d. (American Journal of Islam and Society, 1995)
The International Islamic Calendar Programme relies on calculationsof the new moon's expected visibility. The term "new moon's visibility"gives a wrong connotation, because the astronomical term "new moon"refers to a moon that is completely dark and invisible. Therefore, fromhere on the term "crescent moon" or simply "crescent" will be used for amoon that could be visible after the new moon phase.The problem of predicting the crescent moon's visibility has been ofinterest to astronomers in general for a friendly competition of sightinga young crescent moon and to Muslims for their needs associated withthe Islamic calendar. The earliest astronomical criterion for visibilityappeared in the Babylonian era: the moon's age after conjunction mustbe more than 24 hours, an arc of separation as must be more than 12° orthe moon sets 48 minutes after sunset. Hindus (500-700 C.E.) developeda more elaborate system of calculations with the same as >= 12° criterion.In the eighth to tenth centuries C.E., Muslim astronomers, notablyYa'qub ibn Tariq, Habash, al Khwarizmi, al Farghani, and al Battaniexcelled in mathematical astronomy and developed rules for predictingthe crescent's visibility based on the importance of the crescent's width.A century later, al Biruni recommended al Battani's procedures. In thefifth century, al Sufi and al Kashani still quoted the early Babylonian criterionof as >=12° .In the late part of the nineteenth century, Schmidt recorded observationsin Athens, Greece, throughout a period of twenty years. Fotheringham(1910) and Maunder (1911), who used Schmidt's data and thenadded some more observational data, made the first significant developmentsin criterion for visibility since the time of al Battani. Bruin (1977)developed an independent physics-based criterion involving such variablesas the sky's brightness, contrast, the crescent's intensity, and so on.However, his criterion was only theoretical and its validity needed to beproven by actual observations. Ilyas (1981) modified Bruin's criterion inorder to remove the discrepancy in his method and the actual observationalcriterion of Maunder. All of these suggested criteria for calculatingexpected visibility have been summarized in a tabular form on page15 ...